Spatial distribution of heavy hydrocarbons, PAHs and metals in polluted areas. The case of "Galicia", Spain. Issue 1 (15th August 2017) - Monaco, D.; Chianese, E.; Riccio, A.; Delgado-Sanchez, A.; Lacorte, S.
Abstract: The aim of this work is to verify the impact of anthropogenic activities and the effects of accidental events, e.g. oil spills, on the marine environment. For this reason, marine sediments and soil samples were collected in the inner part of Vigo and Pontevedra bays, in the Galicia region, northwest Spain, an area interested by many events of oil spills and also characterized by coastal areas with intense anthropic activities; also Cíes Islands, a natural protected area facing the Vigo bay, was investigated, as background site. PAHs, heavy hydrocarbons and metals were analyzed according to standard methods, in order to satisfy quality assurance and quality check constraints. Total PAHs concentration (Σ16 compounds) were in the range of 25–4000 ng/g, and 30–800 ng/g for marine sediments and soil samples, respectively. Even some samples from the Cíes Islands, show a contamination with values achieving > 200 ng/g of PAHs. Although contamination levels have been shown to be strong at several locations in the study area, their ranges are those typical of other estuarine sites, with PAHs and hydrocarbons primarily of pyrolytic origin. This observation was further confirmed by enrichment factors of some metals (Cd, Cu, Pb and Zn) that match to those of harbor and shipyard zones of the main industrial and commercial maritime areas. Highlights: PAHs, heavy hydrocarbons and metals were analyzed. Diagnostic ratios for PAHs point to a pyrolitic origin. Enrichment factors for metals indicate contaminated conditions.